Implications of knee crepitus to the overall clinical presentation of women with and without patellofemoral pain. (September 2018) - de Oliveira Silva, Danilo; Barton, Christian; Crossley, Kay; Waiteman, Marina; Taborda, Bianca; Ferreira, Amanda Schenatto; Azevedo, Fábio Mícolis de
Abstract: Objectives: Compare anthropometric characteristics, function, kinesiophobia, catastrophism and knee extensor strength between women (i) with PFP and crepitus (PFPcrepitus ); (ii) with PFP and no crepitus (PFPNOcrepitus ); (iii) without PFP and crepitus (Pain-freecrepitus ); and (iv) without PFP and no crepitus (Pain-freeNOcrepitus ). Design: Cross-sectional. Setting: Laboratory study. Participants: 65 women with PFP and 51 pain-free women. Main outcome measures: Objective assessment of knee crepitus, forward step-down and single leg hop tests; knee extensor strength tests; and subjective ratings of function, kinesiophobia, pain catastrophising and knee stiffness. Results: Crepitus was more common in women with PFP (50.7%) compared to those without (33.3%) ( χ ( 1 ) 2 = 4.17 ; p = 0.031 ) . PFPcrepitus and PFPNOcrepitus groups had lower self-reported function; and higher kinesiophobia, catastrophism and knee stiffness compared to Pain-freecrepitus and Pain-freeNOcrepitus groups (p < 0.001). PFPcrepitus, PFPNOcrepitus and Pain-freecrepitus groups had lower functional performance compared to the Pain-freeNOcrepitus group (p < 0.040). PFPcrepitus and PFPNOcrepitus groups had lower isometric, concentric and eccentric knee extensor strength compared to the Pain-freeNOcrepitus group (p < 0.041), but not the pain-freecrepitus group. PFPcrepitus presented higher BMI than other groups (p = 0.001). Conclusion: Kinesiophobia, catastrophism, knee stiffness, strength and physical function are all impaired in women with PFP, regardless of crepitus. In pain-free women, crepitus was associated with poorer objective function. Highlights: Knee crepitus does not affect physical function or strength in PFP. Knee crepitus does not affect kinesiophobia or pain catastrophism in PFP. Pain-free people with crepitus present poorer objective function.